World heritage designation and property: the impact of preservation on the price of historic assets - Salinger, Eyal; Shefer, Daniel; Mualam, Nir (International Journal of Strategic Property Management, 2022)
The restrictions and requirements imposed by historic preservation regulations bring about many changes to the rights of property owners. They might impose additional costs, most notably by prohibiting the demolition of designated buildings and thus decreasing property-development opportunities. The objective of this study is to examine what happens following world heritage designations; specifically, if and how such designations impact the property values of historic buildings. Using the hedonic price method, we measure the value of the option to demolish and rebuild that is denied to owners of designated buildings. We also measure the value of preservation regulations, expressed in the prices of apartments in designated buildings. The study area is the “White City” of Tel Aviv, which UNESCO designated as a world heritage site. The findings suggest that the market price of a designated building is on average 12.5% lower than its theoretical value if the building was not subject to historic preservation regulations. Moreover, a premium of approximately 14% was found in the price of apartment units in designated buildings if the building underwent preservation. These findings could have a direct impact on public policies designed to promote the preservation of historical buildings in world heritage sites.